Dual Reporter Gene Imaging - Jiantu Che; Mikhail Doubrovin; Inna Serganova; Ludmila Ageyeva; Pat Zanzonico; Ronald Blasberg (Molecular Imaging)
The human and rodent sodium iodide symporters ( NIS ) have recently been cloned and are being investigated as potential therapeutic and reporter genes. We have extended this effort by constructing an internal ribosomal entry site (IRES)-linked human NIS (hNIS) -enhanced green fluorescent protein ( eGFP ) hybrid reporter gene for both nuclear and optical imaging. A self-inactivating retroviral vector, termed pQCNIG, containing hNIS-IRES-eGFP dual reporter gene, driven by a constitutive CMV promoter, was constructed and used to generate RG2-pQCNIG cells and RG2-pQCNIG tumors. 131 I-iodide and 99m TcO 4 -pertechnetate accumulation studies plus fluorescence microscopy and intensity assays were performed in vitro, and gamma camera imaging studies in RG2-pQCNIG and RG2 tumor-bearing athymic rats were performed. RG2-pQCNIG cells expressed high levels of hNIS protein and showed high intensity of eGFP fluorescence compared with RG2 wild-type cells. RG2-pQCNIG cells accumulated Na 131 I and 99m TcO 4 – to a 50:1 and a 170:1 tissue/medium ratio at 10 min, compared with 0.8:1.2 tissue/medium ratio in wild-type RG2 cells. A significant correlation between radiotracer accumulation and eGFP fluorescence intensity was demonstrated. RG2-pQCNIG and RG2 tumors were readily differentiated by in vivo gamma camera imaging; radiotracer uptake increased in RG2-pQCNIG but declined in RG2 tumors over the 50-min imaging period. Stomach and thyroid were the major organs of radionuclide accumulation. The IRES-linked hNIS-eGFP dual reporter gene is functional and stable in transduced RG2-pQCNIG cells. Optical and nuclear imaging of tumors produced from these cell lines provides the opportunity to monitor tumor growth and response to therapy. These studies indicate the potential for a wider application of hNIS reporter imaging and translation into patient studies using radioisotopes that are currently available for human use for both SPECT and PET imaging.